Effect of ski binding parameters on knee biomechanics: A three-dimensional computational study - St. Onge, N.; Chevalier, Y.; Hagemeister, N.; van De Putte, M.; de Guise, J. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION: Downhill skiing is a relatively safe sport, but many potentially avoidable injuries do occur. Whereas tibia and ankle injuries have been declining, severe knee sprains usually involving the anterior cruciate ligament (ACL) have increased from the 1970s to the 1990s. The goal of the present study was to evaluate the effect of the position of the binding pivot point and binding release characteristics on ACL strain during a phantom-foot fall. METHODS: We computed ACL strain using a biomechanical computer knee model to simulate the phantom-foot ACL-injury mechanism. This mechanism, which is one of the most common mechanisms of ACL injury in downhill skiing, occurs when the weight of the skier is on the inner edge of the ski during a backward fall, resulting in a sharp uncontrolled inward turn of the ski. RESULTS: The model predicts, that under simulated phantom-foot conditions, a binding with fast-release characteristics with a pivot positioned in front of the center of the boot produces less strain on the ACL. Current bindings have their pivot point approximately at the center of the heel radius. A pivot positioned at the back of the binding is more effective for sensing loads that occur at the tip of the ski. However, it is less effective for sensing loads that occur at the tail of the ski and, therefore, offers less protection during a phantom-foot fall. CONCLUSION: A binding with two pivot points, one positioned in front and the other at the back, could sense twist loads applied to the ski both at the front and at the back, and might, therefore, be a solution to reduce the occurrence of ACL injuries.